2017
DOI: 10.1080/08870446.2017.1357814
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of worries about modern health hazards: Experimental evidence for a conjoint influence of media reports and personality traits

Abstract: The results of both studies reveal a significant and specific influence of sensational short mass media reports on MHW. The influence of potential moderators such as absorption remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…It is important to note, however, that sample size may also play a considerable role in the interaction between the type of video viewed and symptom score, and a larger sample size would have increased the chance of identifying an effect of the video in the present study. In line with previous research, the present study also found that participants who viewed the alarmist video had a larger increase in state anxiety and risk perception from baseline relative to those who viewed the control video (Bräscher, Raymaekers, et al, 2017;Witthöft et al, 2017;Witthöft & Rubin, 2013). This provides further support to the notion that sensationalized media reports are capable of increasing people's concerns and worries about exposure to EMF.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is important to note, however, that sample size may also play a considerable role in the interaction between the type of video viewed and symptom score, and a larger sample size would have increased the chance of identifying an effect of the video in the present study. In line with previous research, the present study also found that participants who viewed the alarmist video had a larger increase in state anxiety and risk perception from baseline relative to those who viewed the control video (Bräscher, Raymaekers, et al, 2017;Witthöft et al, 2017;Witthöft & Rubin, 2013). This provides further support to the notion that sensationalized media reports are capable of increasing people's concerns and worries about exposure to EMF.…”
Section: Discussionsupporting
confidence: 91%
“…Although a number of studies have shown that explicit suggestions about the adverse effects of EMF exposure can increase concern and negatively influence people's beliefs about EMF exposure (Barnett et al, 2007;Köteles et al, 2016;Nielsen et al, 2010;Wiedemann et al, 2014;Wiedemann et al, 2013;Wiedemann & Schütz, 2005;Wiedemann et al, 2006;Witthöft et al, 2017) (factors which are considered to be key in contributing to a nocebo response (Webster et al, 2016)), it has remained relatively unclear whether the negative randomized, counterbalanced trials were conducted. By demonstrating that the experiment contained a 'no exposure' condition, the present study was able to more clearly determine whether any observed increases in symptoms were the result of a nocebo effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak to medium level associations between the four constructs also support this view. Moreover, no association between MHWs and negative affect was found in healthy participants in several studies 9,24 , thus the finding that MHWs are increased in individuals with high level of negative affect represent an important contribution to the literature. Of course, the above mentioned cognitive distortions might directly contribute to the worrying tendency and increase MHWs.…”
Section: Discussionmentioning
confidence: 97%
“…This finding can be explained by two approaches. First, stories about harmful effects of modern technologies are abundant in mass media and impact not only people's worrying tendency (Bräscher, Raymaekers, Van den Bergh, & Witthöft, 2017;Petrie et al, 2001;Witthöft et al, 2018), but also their automatic self-perception and self-categorization. Second, as in the case of complementary and alternative medicine (Astin, 1998), philosophical congruence might be a motive for those characterized by an experiential-intuitive thinking style to accept the IEI-EMF label, even in the absence of symptoms.…”
Section: Assessing Iei-emfmentioning
confidence: 99%